Season and environment modulate aquatic invertebrates’ responses to trout and indigenous fishes in three South African mountain streams - Bellingan, Terence A.; Hugo, Sanet; Villet, Martin H.; Weyl, Olaf L. F. (Frontiers in Environmental Science, 2022)
Introduced organisms are seen as one of the greatest threats to resource sustainability worldwide, and aquatic macroinvertebrates are regarded as good indicators of the health of water resources. To explore these two perspectives, the responses of macroinvertebrate faunas to native and introduced fishes in three headwater tributaries of the Keiskamma River system, South Africa, were examined by comparing potential indicator communities in reaches considered to be fishless, reaches invaded by introduced salmonid species, and reaches containing native fishes. Patterns in the macroinvertebrate faunal assemblage data were driven strongly by season and flow rate, and less strongly by the presence of insectivorous fishes and biotope availability, a finding in parallel with several similar studies from the region. This affirms that aquatic macroinvertebrate faunas are responsive indicators of both environmental and biotic factors and leaves room for further studies to resolve the effects of non-native fish in the Keiskamma River system and other similar systems from South Africa.